High School and Preservice Chemistry Teacher Education Students’ Understanding of Voltaic and Electrolytic Cell Concepts: Evidence of Consistent Learning Difficulties Across Years - Rahayu, S.; Treagust, David; Chandrasegaran, Chandra (2021)
High school students learn the basic voltaic and electrolytic cell concepts during their last year prior to entering an undergraduate teacher-education science degree. During the 4 years of university, students complete a sequence of topics designed to build on conceptual understanding presented in previous years. At the end of their degrees, graduating students are expected to have developed a comprehensive understanding of the subject that they are required to teach. In this research, we designed and developed a 12-item diagnostic instrument which addressed 10 propositional content knowledge statements based on the grade 12 chemistry curriculum that will be taught. In this cross-section study, 50 grade 12 high school students and 216 preservice chemistry teacher education undergraduates in years 1–4 responded to the Electrochemistry Conceptual Test (ECT) consisting of 12 two-tier multiple-choice items. The instrument was content validated by authors and peers prior to administration and when implemented had a Cronbach alpha reliability coefficient of 0.64. Overall, the students across years possessed basic knowledge about electrochemical cells but frequently were unable to explain their knowledge. While the grand mean trend in understanding electrochemistry concepts from high school through university study did show some improvement, the mean scores remained relatively low, and the year group means per item showed no such trend exacerbated by items having varying levels of difficulty. Based on this research, the lack in understanding about electrochemical concepts suggests that instruction in high school and ongoing university chemistry education faces ongoing challenges.